2023
DOI: 10.1038/s41392-023-01358-y
|View full text |Cite
|
Sign up to set email alerts
|

Simplified algorithm for genetic subtyping in diffuse large B-cell lymphoma

Abstract: Genetic classification helps to disclose molecular heterogeneity and therapeutic implications in diffuse large B-cell lymphoma (DLBCL). Using whole exome/genome sequencing, RNA-sequencing, and fluorescence in situ hybridization in 337 newly diagnosed DLBCL patients, we established a simplified 38-gene algorithm (termed ‘LymphPlex’) based on the information on mutations of 35 genes and rearrangements of three genes (BCL2, BCL6, and MYC), identifying seven distinct genetic subtypes: TP53Mut (TP53 mutations), MCD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 48 publications
0
38
0
Order By: Relevance
“…13 In the era of immunochemotherapy, non-GCB DLBCL, a high IPI score and MCD-like subtype are all predictors of a poor prognosis for patients with DLBCL. [23][24][25][26][27] Our study suggests that a therapeutic regimen containing BTKis, compared with the standard regimen, can significantly improve the CRR in DLBCL patients with the above high-risk factors. A subgroup analysis of 18 patients in the BTKi + R-CHOP treatment group suggested that there were no statistically significant differences in ORR, CRR and PFS between GCB versus non-GCB DLBCL, non-DEL versus DEL or IPI ≥3 versus <3.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…13 In the era of immunochemotherapy, non-GCB DLBCL, a high IPI score and MCD-like subtype are all predictors of a poor prognosis for patients with DLBCL. [23][24][25][26][27] Our study suggests that a therapeutic regimen containing BTKis, compared with the standard regimen, can significantly improve the CRR in DLBCL patients with the above high-risk factors. A subgroup analysis of 18 patients in the BTKi + R-CHOP treatment group suggested that there were no statistically significant differences in ORR, CRR and PFS between GCB versus non-GCB DLBCL, non-DEL versus DEL or IPI ≥3 versus <3.…”
Section: Discussionmentioning
confidence: 70%
“…Based on NGS and FISH results, the MCD-like, ST2-like, BN2-like, TP53mut subtypes were defined using the LymphPlex classification tool. 23 The last follow-up was on June 30, 2023.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…A homemade pipeline was used to filter indels and SNVs detected by the above software 25 based on the following criteria: (1) variants with a mapping quality >30 were retained; (2) SNVs or indels with a mutation allele frequency <0.001 in the 1000 Genomes Project, ExAC-ALL, or ExAC East Asian databases were retained 26 ; (3) SNVs or indels with a variant allele frequency ≥1% and a read depth >10 were retained; (4) dbSNP (v147) sites in the COSMIC database were retained 27 ; (5) SNPs or indels, including stopgain, stoploss, frameshift, nonframeshift, and splicing sites, were retained; (6) missense mutations predicted as pathogenic at least by one in silico prediction tool (SIFT, Polyphen2_HDIV, Polyphen2_HVAR, LRT, MutationTaster, MutationAssessor, FATHMM, PROVEAN, FATHMM-MKL_coding, MetaSVM, or MetaLR) were retained; and 7 duplicate frameshift mutations in multiple samples, variants found in repetitive regions, and variants found in regions with poor coverage were excluded. Because the paired normal samples were not sequenced, all nonsilent SNVs/ indels yielded from the filtering pipeline were manually reviewed (see Table S2).…”
Section: Massive Parallel Sequencing and Variant Callingmentioning
confidence: 99%
“…The three antibodies CD10, BCL6, and MUM1 are used by Han's algorithm to classify DLBCL into germinal center B-cell-like (GCB) and nonGCB, which enables physicians to determine the prognosis of DLBCL patients (Alizadeh et al, 2000;Rosenwald et al, 2002). Next-generation sequencing was used to assess the genetic landscape of DLBCL (Chapuy et al, 2018;Schmitz et al, 2018;Shen et al, 2023;Wright et al, 2020). The LymphGen algorithm identi es seven distinct genetic subtypes, which is wildly acceptable, including MCD, BN2, N1, EZB-MYC +/− , ST2, and A53 (Shen et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Next-generation sequencing was used to assess the genetic landscape of DLBCL (Chapuy et al, 2018;Schmitz et al, 2018;Shen et al, 2023;Wright et al, 2020). The LymphGen algorithm identi es seven distinct genetic subtypes, which is wildly acceptable, including MCD, BN2, N1, EZB-MYC +/− , ST2, and A53 (Shen et al, 2023). Recently, a simpli ed 38-gene algorithm (termed 'LymphPlex') based on the information on mutations of 35 genes and rearrangements of three genes were established (Schmitz et al, 2018).…”
Section: Introductionmentioning
confidence: 99%